Pengaturan Torsi Motor Induksi 3 Phasa Menggunakan Direct Torque Control - Alvin Tri Nugroho; Yuliyanto Agung Prabowo (Universitas Indraprasta PGRI Jakarta, 2022)
The three-phase induction motor is the most widely used drive in the industry due to its sturdy construction and relatively affordable price. However, there is a disadvantage that it is difficult to control torque and speed dynamically and separately. The torque and speed characteristics of the three-phase induction motor are a couple and are nonlinear. So it is difficult to be able to control torque and speed separately. To overcome these problems, there is a decoupling control method that will separate the control between torque and speed using DTC (Direct Torque Control) by setting the value of the stator flux as a sector selector switching. DCT is a form of vector control. The least square estimation method is used for speed forecasting on induction motors through measurement data of stator flux and rotor flux which are regressed into non-linear form to monitor motor speed. Based on tests using simulations, the results show that when an induction motor is given a torque load, the torque response changes (tracking) the torque response of the induction motor can follow these changes. Where the characteristic value of the response transient, time constant (?) is 0.082 seconds, the rise time (TR) is 0.242 seconds and the settling time (TS) is 0.246 seconds.